The Order in the Growth of the Injective and Super-Increasing Vectors Knapsacks Quantity - D. M. Murin (Моделирование и анализ информационных систем)
In 1978 R. Mercle and M. Hellman offered to use the subset sum problem for constructing cryptographic systems. The proposed cryptosystems were based on a class of the knapsacks with super-increasing vectors. This class is a subset of the set of knapsacks with injective (cryptographic) vectors that allow the single-valued decoding (decryption) result. In this paper we consider the problems related to the order in the growth of the injective vectors knapsacks quantity and to the order in the growth of knapsacks quantity with the super-increasing vectors through the knapsack maximal element increasing.